Congenital Dorsal Dermal Sinus, A Rare Entity: diagnosis and Management (Bangladesh Journal of Neurosurgery, 2022)
Congenital dorsal dermal sinus is a rare occult spinal dysraphism. It may be associated with other cutaneous manifestations and spinal pathologies. Patients either presents with infection or neurological problems. We present a case presented with dorsal dermal sinus with discharging sinus with split cord with block vertebra with hypertrichosis and hairy melanocytic naevus.Bang. J Neurosurgery 2021; 11(1): 45-49